Исследование Новобогородицкой крепости в 2009 г. - Ковалева, И.Ф.; Шалобудов, В.Н. (Археологічні дослідження в Україні, 2010)
Objects studied by the expedition of the O. Honchar Dnipropetrovsk National University at the territory of the Late Mediaeval Novobohorodytska fortress are described.